Korelasi lingkar pinggang dan rasio lingkar pinggang-panggul terhadap kadar glukosa plasma menggunakan tes toleransi glukosa oral - Farida Dwi Rokhmah; Dian Handayani; Harun Al-Rasyid (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2015)
Background: The increased circumference of waist and waist-hip ratio describe intra-abdominal fat which is associated with a number of metabolic disorders such as diabetes mellitus.Objective: The aim of the study is to analyze the correlation between the circumference of waist and waist-hip ratio in plasma glucose levels using the Oral Glucose Tolerance Test (OGTT) method in adults.Method: This study was a cross-sectional study involving 75 respondents from Klojen which is located in Malang and obtained by multistage sampling random. The variables in the study include circumference of waist, waist-hip ratio, fasting plasma glucose and plasma glucose after consuming glucose liquid. Data were analyzed using coefficient contingency and Spearman correlation.Results: This study found that based on waist circumference and waist-hip ratio, most of the subjects are categorized as not at risk. Furthermore, based on plasma glucose level measurement using OGTT, 96% of subjects are normal.Conclusion: There is no correlation between plasma glucose level using OGTT and waist circumference as well as waist-hip ratio (p>0.05).